Effects of outdoor ranging on external and internal health parameters for hens from different rearing enrichments - Md Saiful Bari; Yan C.S.M. Laurenson; Andrew M. Cohen-Barnhouse; Stephen W. Walkden-Brown; Dana L.M. Campbell (PeerJ, 2020)
In Australia, free-range layer pullets are typically reared indoors, but adult layers go outdoors, and this mismatch might reduce adaptation in laying environments. Enrichments during rearing may optimise pullet development and subsequent welfare as adult free-range hens. In the outdoor environment, hens may have greater opportunities for exercise and natural behaviours which might contribute to improved health and welfare. However, the outdoor environment may also result in potential exposure to parasites and pathogens. Individual variation in range use may thus dictate individual health and welfare. This study was conducted to evaluate whether adult hens varied in their external and internal health due to rearing enrichments and following variation in range use. A total of 1386 Hy-Line Brown® chicks were reared indoors across 16 weeks with three enrichment treatments including a control group with standard housing conditions, a novelty group providing novel objects that changed weekly, and a structural group with custom-designed structures to increase spatial navigation and perching. At 16 weeks of age the pullets were moved to a free-range system and housed in nine identical pens within their rearing treatments. All hens were leg-banded with microchips and daily ranging was assessed from 25 to 64 weeks via radio-frequency identification technology. At 64–65 weeks of age, 307 hens were selected based on their range use patterns across 54 days up to 64 weeks: indoor (no ranging), low outdoor (1.4 h or less daily), and high outdoor (5.2–9 h daily). The external and internal health and welfare parameters were evaluated via external assessment of body weight, plumage, toenails, pecking wounds, illness, and post-mortem assessment of internal organs and keel bones including whole-body CT scanning for body composition. The control hens had the lowest feather coverage (p < 0.0001) and a higher number of comb wounds (P = 0.03) than the novelty hens. The high outdoor rangers had fewer comb wounds than the indoor hens (P = 0.04), the shortest toenails (p < 0.0001) and the most feather coverage (p < 0.0001), but lower body weight (p < 0.0001) than the indoor hens. High outdoor ranging decreased both body fat and muscle (both p < 0.0001). The novelty group had lower spleen weights than the control hens (P = 0.01) but neither group differed from the structural hens. The high outdoor hens showed the highest spleen (P = 0.01) and empty gizzard weights (P = 0.04). Both the rearing enrichments and ranging had no effect on keel bone damage (all P ≥ 0.19). There were no significant interactions between rearing treatments and ranging patterns for any of the health and welfare parameters measured in this study (P ≥ 0.07). Overall, rearing enrichments had some effects on hen health and welfare at the later stages of the production cycle but subsequent range use patterns had the greatest impact.